Analisis Kebijakan Pajak Penghasilan untuk UMKM Pasca Terbitnya Undang-Undang Nomor 7 Tahun 2021 Tentang Harmonisasi Peraturan Perpajakan - Made Laksmi Sena Hartini; Putu Ayu Meidha Suwandewi (Penerbit Goodwood, 2022)
Purpose: The motivation behind this study is to decide the implication of Income Tax treatment for Micro, Small and Medium Enterprises (MSMEs) after the issuance of the new tax regulation of Tax Law No. 7 Year 2021 concerning Tax Regulation Harmonization. Method: This study utilizes an exploratory and descriptive methodology. The exploration method utilized is literature study, to be specific by collecting and reading works as books, journals, articles, and the Taxation Law and its carrying out guidelines. Results: The results of this study are there was significant change in Income Tax calculation if it is compared to previous regulation especially for personal taxpayer of MSMEs and there is a reduction in the amount of tax that must be paid by the MSMEs taxpayer. Limitations: The lack of supporting literature obtained by the authors regarding data on the development of MSMEs in Indonesia in 2020 also this study only carried out of Income Tax implication aspect of the Law Number 7 of 2021 concerning Tax Regulation Harmonization. Contribution: This research is expected to contribute for MSMEs and can be utilized as a kind of perspective for additional scientists.